Be my guest : english for the hotel industry - O'Hara, Francis (Singapore : Cambridge University Press, 2009)
Be My Guest is a language course for pre and in-service students of English in the hotel industry at the elementary to lower intermediate level.
1 Introductions -- 2 The Check-in -- 3 The hotel bedroom -- 4 The bathroom & porter -- 5 Services in the hotel -- 6 Location of facilities -- 7 Room services -- 8 Problems and solutions -- 9 Taking bar orders -- 10 In the restaurant (1) -- 11 In the restaurant (2) -- 12 Interesting places to visit -- 13 Enquiries -- 14 Using the phone -- 15 The check-out
Keywords: ENGLISH LANGUAGE -- SPOKEN ENGLISH -- TEXTBOOKS FOR FOREIGN SPEAKERS